2016
DOI: 10.1089/fpd.2015.2082
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification of thesefAGene for Rapid Detection ofSalmonellaEnteritidis andSalmonellaGallinarum in Chickens

Abstract: Salmonella spp. pose a threat to both human and animal health, with more than 2600 serovars having been reported to date. Salmonella serovars are usually identified by slide agglutination tests, which are labor intensive and time consuming. In an attempt to develop a more rapid screening method for the major poultry Salmonella serovars, we developed a loop-mediated isothermal amplification (LAMP) assay, which directly detected the sefA gene, a fimbrial operon gene existing in several specific serovars of Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…b). These results indicated that the sensitivity of the LAMP assay for P. shigelloides detection was 10 times higher than that of conventional PCR, consistent with the results of previous LAMP assays (Wang et al ; Gong et al ). Furthermore, compared to conventional PCR, the LAMP method allowed faster visualization of results by employing calcein or NADA instead of gel electrophoresis.…”
Section: Resultssupporting
confidence: 90%
“…b). These results indicated that the sensitivity of the LAMP assay for P. shigelloides detection was 10 times higher than that of conventional PCR, consistent with the results of previous LAMP assays (Wang et al ; Gong et al ). Furthermore, compared to conventional PCR, the LAMP method allowed faster visualization of results by employing calcein or NADA instead of gel electrophoresis.…”
Section: Resultssupporting
confidence: 90%
“…For instance, sdfI (Yang et al , 2010 ) and prot6E (Hu et al , 2018 ) were used to design two separate LAMP assays for Salmonella enterica serovar Enteritidis, while typh was used to specifically detect Salmonella Typhimurium (Kumar et al , 2014 ). The sefA gene has been explored to design a LAMP assay for both Salmonella Enteritidis and Salmonella Gallinarum (Gong et al , 2016 ). An insertion element IS200/IS1351 gene was used to detect Salmonella O9 serogroup (Okamura et al , 2008 ), prt ( rfbS ) for serogroup D (i.e., O9) (Ravan and Yazdanparast 2012a , b), and rfbJ for O4 serogroup (Okamura et al , 2009 ).…”
Section: Salmonella Lamp Assay Developmentmentioning
confidence: 99%
“…For example, emerging technologies have been proposed for rapid viral or bacterial disease diagnoses in the clinical diagnostic field. These include rapid water‐based thermal cyclers (Wong et al, ) or reverse transcription‐loop‐mediated isothermal amplification (RT‐LAMP) (Gong et al, ; Liu et al, ). For clinical samples, these methodologies have proven to be low‐cost, and just as sensitive as traditional QPCR or RT‐PCR methods.…”
Section: Viral Detectionmentioning
confidence: 99%